Exercise management in type 1 diabetes: a consensus statement. Issue 5 (May 2017) - Riddell, Michael C; Gallen, Ian W; Smart, Carmel E; Taplin, Craig E; Adolfsson, Peter; Lumb, Alistair N; Kowalski, Aaron; Rabasa-Lhoret, Remi; McCrimmon, Rory J; Hume, Carin; Annan, Francesca; Fournier, Paul A; et al.
Summary: Type 1 diabetes is a challenging condition to manage for various physiological and behavioural reasons. Regular exercise is important, but management of different forms of physical activity is particularly difficult for both the individual with type 1 diabetes and the health-care provider. People with type 1 diabetes tend to be at least as inactive as the general population, with a large percentage of individuals not maintaining a healthy body mass nor achieving the minimum amount of moderate to vigorous aerobic activity per week. Regular exercise can improve health and wellbeing, and can help individuals to achieve their target lipid profile, body composition, and fitness and glycaemic goals. However, several additional barriers to exercise can exist for a person with diabetes, including fear of hypoglycaemia, loss of glycaemic control, and inadequate knowledge around exercise management. This Review provides an up-to-date consensus on exercise management for individuals with type 1 diabetes who exercise regularly, including glucose targets for safe and effective exercise, and nutritional and insulin dose adjustments to protect against exercise-related glucose excursions.